Entrepreneurship and economic growth - Audretsch, David B.; Keilbach, Max C., 1962-; Lehmann, Erik.; Oxford eBooks (Oxford : Oxford University Press, 2006)
By serving as a conduit for knowledge spillovers entrepreneurship is the missing link between investments in knowledge & economic growth. Entrepreneurship is an important mechanism permeating the knowledge filter to facilitate the spill over of knowledge & ultimately generate economic growth.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Entrepreneurship; Creative ability in business; Small business -- Technological innovations; Technological innovations -- Economic aspects; Diffusion of innovations -- Economic aspects; Economic development; Electronic books